Restructuring the Regulation on the Crucial Role of Advocates in Realizing an Integrated Criminal Justice System in Indonesia - Ridwan Anthony Taufan; Boy Nurdin (Yayasan Adra Karima Hubbi, 2024)
The position and role of advocates are crucial in realizing an integrated criminal justice system in Indonesia. Advocates serve as a bridge for ensuring access to justice and protecting the legal rights of individuals, but their role often faces challenges due to a lack of effective coordination among law enforcement agencies. This research aims to analyze the critical role of advocates in improving the criminal justice system’s responsiveness and coherence. Using a normative legal research method, the study examines relevant regulations, particularly Law No. 18 of 2003 on Advocates, and explores their practical application through legal literature and secondary data analysis. The findings highlight that advocates play an essential role in fostering coordination among key elements of the justice system, including the police, prosecutor’s office, and judiciary. However, the study identifies significant challenges in optimizing their contributions, such as regulatory gaps and insufficient collaboration frameworks. Strengthening the regulation and coordination mechanisms for advocates is imperative for achieving a more integrated and effective criminal justice system. In conclusion, enhancing the advocate’s role as a law enforcer will contribute to a fairer and more efficient justice system in Indonesia.